2009
DOI: 10.2353/ajpath.2009.081016
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Requires Sphingosine-1-Phosphate Type 1 Receptors to Induce Angiogenic Genes and Endothelial Cell Remodeling

Abstract: Arsenic in drinking water is a major public health concern as it increases risk and incidence of cardiovascular disease and cancer. Arsenic exposure affects multiple vascular beds, promoting liver sinusoidal capillarization and portal hypertension, ischemic heart disease, peripheral vascular disease, and tumor angiogenesis. While Rac1-GTPase and NADPH oxidase activities are essential for arsenic-stimulated endothelial cell signaling for angiogenesis or liver sinusoid capillarization, the mechanism for initiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 60 publications
3
30
0
Order By: Relevance
“…The cells were laid on top of Histopaque-1083 (Sigma) and centrifuged at 2000 rpm for 10 min at room temperature to obtain low density BM (LDBM) cells. Murine embryonic fibroblasts and human vascular endothelial cells (HMVECs) were obtained and cultured as described elsewhere (31,32).…”
Section: Methodsmentioning
confidence: 99%
“…The cells were laid on top of Histopaque-1083 (Sigma) and centrifuged at 2000 rpm for 10 min at room temperature to obtain low density BM (LDBM) cells. Murine embryonic fibroblasts and human vascular endothelial cells (HMVECs) were obtained and cultured as described elsewhere (31,32).…”
Section: Methodsmentioning
confidence: 99%
“…As III -induced pathophysiological remodeling of LSECs (defenestration/capillarization and platelet/endothelial cell adhesion molecule-1 expression) is also attenuated variously by Nox2ds-tat, genetic deletion of p47 phox and selective pharmacological inhibition of Rac1 (Straub et al, 2008). Furthermore, studies of human microvascular ECs and LSECs have revealed that As III activates a pertussis toxin-sensitive G protein (i.e., G i )-coupled pathway to induce Rac1 translocation (Straub et al, 2009) (Fig. 3).…”
Section: Arsenic and Nox2mentioning
confidence: 99%
“…3). Indeed, As III -induced angiogenic gene expression in human microvascular ECs is prevented by pharmacological blockade or siRNA knockdown of sphingosine-1-phosphate type 1 receptors (S1PR 1 ) (Straub et al, 2009), and blockade of S1PR 1 s prevents both S1P-and As III -induced ROS formation in LSECs (Straub et al, 2009). Pertussis toxinsensitive As III -induced differentiation of human mesenchymal stem cells, however, is unaffected by blockade of S1PR 1 s, but is prevented in a cumulative fashion by selective blockers of endothelin-1 type A and B receptors (Klei et al, 2013).…”
Section: Arsenic and Nox2mentioning
confidence: 99%
“…Previous studies showed that short term arsenic exposure causes Rac1 activation in endothelial cells and Rac1 activity is required for arsenic-stimulated endothelial cell remodeling and angiogenesis (46,47). However, whether Rac1 is activated in cells malignantly transformed by long term arsenic exposure and whether Rac1 plays a role in arsenic carcinogenesis are not clear.…”
Section: Discussionmentioning
confidence: 92%